Red blood cells motion in a glass microchannel - Pinho, Diana (2010)
The motion of the red blood cells (RBCs) flowing in microvessels and microchannels depend on several effects, such as hematocrit (Hct), geometry, and temperature. According to our knowledge, the effect of the temperature on RBC motion was never investigated at a microscale level. Hence, the aim of the present work is to determine the effect of the temperature on the RBC’s trajectories and to investigate the best approximation of the trajectories through a nonlinear optimization. In vitro human blood was pumped through a 100 mm circular microchannel and by using a confocal micro- PTV system the RBC’s trajectories were measured at different temperatures, i.e., 25◦C and 37◦C. In this study we measured the motion of forty cells flowing in the middle of the microchannel and applied different functions to approximate its behavior.